From Amazonia to southern Africa: atmospheric moisture transport through low‐level jets and atmospheric rivers. Issue 1 (18th September 2018) - Ramos, Alexandre M.; Blamey, Ross C.; Algarra, Iago; Nieto, Raquel; Gimeno, Luis; Tomé, Ricardo; Reason, Chris J.C.; Trigo, Ricardo M.
Abstract: A Lagrangian analysis is applied to identify the main moisture source areas associated with atmospheric rivers (ARs) making landfall along the west coast of South Africa during the extended austral winter months from 1980 to 2014. The results show that areas that provide the anomalous uptake of moisture can be categorized into four regions: (1) the South Atlantic Ocean between 10°S and 30°S, (2) a clear local maximum in the eastern South Atlantic, (3) a continental source of anomalous uptake to the north of the Western Cape, and (4) over South America at a distance of more than 7000 km from the target region. It emerges that the South American moisture source can be linked to a particular phase of the South American low‐level jet, known as a no Chaco jet event (NCJE), which transports moisture to the western and central South Atlantic basin. Concisely, we provide strong evidence that the two margins of the South Atlantic Ocean appear connected by two meteorological structures, with the NCJE playing a key role of transporting moisture from South America to the western and central South Atlantic basin, feeding the AR that transports some of the moisture to the west coast of South Africa. Abstract : Using Lagrangian analysis, performed over the extended austral winter months from 1980–2014, we provide strong evidence that the two continental margins of the South Atlantic Ocean appear connected by two meteorological structures. A no Chaco jet event plays a key role in transporting moisture from South America to the western and central South Atlantic basin, feeding the atmospheric river that transports some of the moisture to the west coast of South Africa.